Ketrampilan Berpikir Kreatif: Suatu Kajian Literatur Sistematik - Triwahyuni Wardhany; Abdul Muhid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Creative thinking needs serious attention because it is one of the essential skills in the 21st Century that supports academic and professional success. This research aims to systematically review the literature regarding strategies for improving creative thinking in students. The study is a Systematic Literature Review (SRL) involving 15 journals published in 2018-2022 and examines the topic of creative thinking skills, improving creative thinking skills, or training creative thinking skills. The journal search was done using a search engine (Google Chrome). The data that has been collected will be analyzed descriptively according to the existing research questions—data analysis using meta-synthesis. The research results show that creative thinking is an idea-construction process emphasizing fluency, flexibility, originality and elaboration. Students' creative thinking abilities can be improved by implementing scientific learning strategies. Several learning models that can improve students' creative thinking abilities include Creative Problem problem-solving, Discovery Learning, Scientific Critical Creative Thinking Model, STEM-E Model, problem-solving learning and Contextual Learning, Problem-Based Learning, project-based Learning, Authentic Learning, and Research-Based Learning